Liver Trauma in the Kitchen: Preparing Whipped Cream with a Siphon Is Not without Risk - Jeremy Bourenne; Béatrice Eon; Fouad Bouzana; Dominique Lambert; Estelle Jean; Pierre Michelet; Marc Gainnier (Case Reports in Critical Care)
We report the case of a 36-year-old woman suffering from liver injury caused by the malfunction of a whipped cream siphon. When this patient handled the whipped cream siphon, the screwed metallic upper part of the siphon was suddenly dissociated from its base and came violently striking her right hypochondrium. At first, the severity of injury was underestimated. Subsequently, due to the persistence of pain experienced by the patient, an abdominal CT scan was performed. It highlighted a severe liver injury with rupture of a branch of the hepatic artery. The evolution was favorable after completion of an embolization and a secondary capsular rupture.